Common Fixed-Point Theorems and c-distance in Ordered Cone Metric Spaces - Rad, Soleimani G.; Rahimi, H. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We present a generalization of several fixed and common fixed point theorems on c -distance in ordered cone metric spaces. In this way, we improve and generalize various results existing in the literature.